If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + -3)(2z + 10)(z + -1) = 0 Reorder the terms: (-3 + z)(2z + 10)(z + -1) = 0 Reorder the terms: (-3 + z)(10 + 2z)(z + -1) = 0 Reorder the terms: (-3 + z)(10 + 2z)(-1 + z) = 0 Multiply (-3 + z) * (10 + 2z) (-3(10 + 2z) + z(10 + 2z))(-1 + z) = 0 ((10 * -3 + 2z * -3) + z(10 + 2z))(-1 + z) = 0 ((-30 + -6z) + z(10 + 2z))(-1 + z) = 0 (-30 + -6z + (10 * z + 2z * z))(-1 + z) = 0 (-30 + -6z + (10z + 2z2))(-1 + z) = 0 Combine like terms: -6z + 10z = 4z (-30 + 4z + 2z2)(-1 + z) = 0 Multiply (-30 + 4z + 2z2) * (-1 + z) (-30(-1 + z) + 4z * (-1 + z) + 2z2 * (-1 + z)) = 0 ((-1 * -30 + z * -30) + 4z * (-1 + z) + 2z2 * (-1 + z)) = 0 ((30 + -30z) + 4z * (-1 + z) + 2z2 * (-1 + z)) = 0 (30 + -30z + (-1 * 4z + z * 4z) + 2z2 * (-1 + z)) = 0 (30 + -30z + (-4z + 4z2) + 2z2 * (-1 + z)) = 0 (30 + -30z + -4z + 4z2 + (-1 * 2z2 + z * 2z2)) = 0 (30 + -30z + -4z + 4z2 + (-2z2 + 2z3)) = 0 Combine like terms: -30z + -4z = -34z (30 + -34z + 4z2 + -2z2 + 2z3) = 0 Combine like terms: 4z2 + -2z2 = 2z2 (30 + -34z + 2z2 + 2z3) = 0 Solving 30 + -34z + 2z2 + 2z3 = 0 Solving for variable 'z'. Factor out the Greatest Common Factor (GCF), '2'. 2(15 + -17z + z2 + z3) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(15 + -17z + z2 + z3)' equal to zero and attempt to solve: Simplifying 15 + -17z + z2 + z3 = 0 Solving 15 + -17z + z2 + z3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4(3x-1.6)=9x-6.4 | | 26=5x^2+7x+2 | | 4.2x-51=2.6x+5 | | y-8.8=8 | | 24/x | | 7(x-9.4)=2.1 | | 2x+27=45 | | 26=(2x+1)(3x+2) | | x^2(2x+3)=17x-12 | | 3/4b=4/6 | | x^3-x^2+5x-2=0 | | (8r+1)(r+2)=0 | | y-23=4y-19 | | 10-2(3x-5)=12 | | 4y-19=y-23 | | 3a+2x= | | x+(x-42)=90 | | (y+20)+(4y-15)=180 | | 4y-19+y-23=2x+27 | | c(3c+2)-3(c^2+4c-17)=1x | | 8(2l+7)=216 | | -1.5/-.3 | | 7n^2+8n+1=0 | | .01/2 | | -2(5n+2)=2 | | k^3-6k^2-21k=0 | | 4(2x-1.7)=4x-6.8 | | 4+35x=15x+16 | | 1/27x^2=4.6875 | | k^2+6k-21=0 | | 3/5w=4/3 | | 27/x^2=4.6875 |